A Novel SPAST Mutation Results in Spastin Accumulation and Defects in Microtubule Dynamics. Issue 3 (20th December 2021) - Chen, Rui; Du, Shiyue; Yao, Yanyi; Zhang, Lu; Luo, Junyu; Shen, Yinhua; Xu, Zhenping; Zeng, Xiaomei; Zhang, Luoying; Liu, Mugen; Yin, Chuang; Tang, Beisha; et al.
ABSTRACT: Background: Haploinsufficiency is widely accepted as the pathogenic mechanism of spastic paraplegia type 4 (SPG4). However, there are some cases that cannot be explained by reduced function of the spastin protein encoded by SPAST . Objectives: To identify the causative gene of autosomal dominant hereditary spastic paraplegia in three large Chinese families and explore the pathological mechanism of a spastin variant. Methods: Three large Chinese hereditary spastic paraplegia families with a total of 247 individuals (67 patients) were investigated, of whom 59 members were recruited to the study. Genetic testing was performed to identify the causative gene. Western blotting and immunofluorescence were used to analyze the effects of the mutant proteins in vitro. Results: In the three hereditary spastic paraplegia families, of whom three index cases were misdiagnosed as other types of neurological diseases, a novel c.985dupA (p.Met329Asnfs*3) variant in SPAST was identified and was shown to cosegregate with the phenotype in the three families. The c.985dupA mutation produced two truncated mutants (mutant M1 and M87 isoforms) that accumulated to a higher level than their wild‐type counterparts. Furthermore, the mutant M1 isoform heavily decorated the microtubules and rendered them resistant to depolymerization. In contrast, the mutant M87 isoform was diffusely localized in both the nucleus and the cytoplasm, could not decorate microtubules, and was not able to promote microtubule disassembly. Conclusions: SPAST mutations leading to premature stop codons do not always act through haploinsufficiency. The truncated spastin may damage the corticospinal tracts through an isoform‐specific toxic effect. Abstract : SPAST mRNA carrying the frameshift mutation c.985dupA was able to produce two stable truncated proteins (truncated M1 and M87 isoforms). The truncated spastin may damage the corticospinal tracts through an isoform‐specific pathological effect, thereby contributing to the pathogenesis of hereditary spastic paraplegia (HSP). © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society